Effectiveness of digital tools for smoking cessation in Asian countries: a systematic review - Goh, Khang Wen; Long, Chiau Ming *; Al-Worafi, Yaser Mohammed; Tan, Ching Siang; Hermansyah, Andi; Rehman, Inayat Ur; Ali, Zahid (Taylor and Francis Group, 2024)
Aim: The use of tobacco is responsible for many preventable diseases and deaths worldwide. Digital interventions have greatly improved patient health and clinical care and have proven to be effective for quitting smoking in the general population due to their flexibility and potential for personalization. However, there is limited evidence on the effectiveness of digital interventions for smoking cessation in Asian countries.